Association between health care facility level and compliance with informative elements of informed consent forms, 2019-2021 - Angeles Fuentes, José Luis (2023)
Objective: To identify the relationship between public health care facility level and compliance with the essential and desired informative elements of informed consent (IC) forms, Lima Metropolitan Area, 2019-2021.Materials and methods: A descriptive and cross-sectional study. A total of 455 IC forms used in public tertiary health care facilities—hospitals (III-1, III-E) and specialized health care institutions (III-2)—were analyzed to assess the compliance of 22 essential and nine desired elements set forth in the current Peruvian laws and regulations and provided by the Inter-American Court of Human Rights (IACHR). This matrix was submitted to the opinion of a group of experts made up of 11 lawyers and health professionals, registering a Kappa coefficient of 1, which implies a “perfect agreement.” In addition, expert competence coefficient (K) was assessed, registering among the specialists an average of 0.92, which represents a “high influence.” Statistical tests such as Spearman's correlation coefficient, chi-square test, Fisher's exact test and Cramér’s phi were performed. Results: IC forms were mostly developed by the specialized health care institutions (66.00 %) and the medical activity (96.90 %) prevailed in said forms. Compliance with the essential (Rho = 0.69) and desired (Rho = 0.64) informative elements showed a significant relationship (p < 0.05) with the health care facility level. The elements "Benefits," "Drug adverse effects,” “Prognosis” and “Recommendations” showed a significant positive relationship (p < 0.05; Φ > 0.00). The elements "Procedure duration," "Contraindications" and "Solution to questions" showed a significant negative relationship (p < 0.05; Φ < 0.00). Conclusions: There is an association between health care facility level and compliance with the essential and desired informative elements of IC forms in public health care facilities in Lima Metropolitan Area between 2019 and 2021.